What is new in the management of the small renal mass in 2023 (Bangladesh Journal of Urology, 2023)
Small renal masses are currently a special clinical entity that require management different from the approaches used for classical renal cell carcinomas. Increasing use of cross-sectional imaging has led to an increase in the diagnosis of incidental small renal masses (SRMs).About 20% of such masses are benign, while a significant proportion of malignant SRMs demonstrate slow growth kinetics and non-aggressive histologic features. Given these characteristics, lesions that were traditionally treated surgically are increasingly managed with less aggressive approaches. Further contributing to the evolving management paradigm is accumulating evidence supporting the safety of active surveillance and the efficacy of percutaneous renal mass biopsy in guiding management decisions.This review discusses the epidemiology and diagnostic work-up of SRMs, the available management options, with emphasis on the clinical factors considered in selecting an appropriate approach. The existing evidence and long-term outcomes of each strategy are discussed. The purpose of this review is to provide the readers with the necessary understanding to appropriately manage this increasingly common condition.Bangladesh J. Urol. 2023; 26(1): 44-51